Numerical analysis of MHD casson fluid flow over an exponentially accelerated vertical plate in embedded porous medium with ramped wall temperature and ramped surface concentration in uniform magnetic field - Ch. Vijaya Bhaskar; Siva Reddy Sheri; Anjan Kumar Suram (International Journal of Applied Power Engineering (IJAPE), 2020)
Numerical analysis of MHD casson fluid flow over an exponentially accelerated vertical plate in embedded porous medium with ramped wall temperature and ramped surface concentration has investigated in the current investigation. The flow governing dimensional velocity, temperature and concentration differential equations are converted into non dimensional form by using non-dimensional variables. Numerical solutions to the converted equations are obtained by finite element method. The results are presented graphically and in tabular form for various controlling parameters. In order to highlig ht the validity and accuracy of our present method, we have compared our results with the results obtained earlier. A very good validation of the present numerical results has been achieved.